2020
DOI: 10.18510/hssr.2020.8456
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Dialogue Journal Writing on the Writing Skills of Jordanian Efl Learners and Their Attitudes Towards Writing

Abstract: Purpose of the study: The purpose of this study is to investigate the impact of dialogue journal writing (DJW) on learning the vocabulary, organization, and grammar of English. It also explores the impact of DJW on the attitudes of students towards writing in English. Methodology: The sample of the study consists of 50 undergraduate Jordanian students divided equally into an experimental and control group. The control group was given traditional writing instruction while the experimental group was taught… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…Al Kayed et al (2020) have, in fact, supported the successful results of several studies conducted earlier. Dabbagh's (2017) study revealed that DJW positively affected students' writing performance and writing components except for language use and mechanics.…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…Al Kayed et al (2020) have, in fact, supported the successful results of several studies conducted earlier. Dabbagh's (2017) study revealed that DJW positively affected students' writing performance and writing components except for language use and mechanics.…”
Section: Introductionsupporting
confidence: 69%
“…3-4, emphasis original) Currently, a number of studies (e.g. Al Kayed, Alkayid & Alsmadi, 2020;Dabbagh, 2017;Hapsari, Susilohadi & Elyono, 2018;Safari, 2020) investigated whether or not DJW was effective in increasing students' writing skills. For instance, Al Kayed et al (2020) investigated the effect of DJW on the writing skills of Jordanian learners of English as a foreign language (EFL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation